S44 Pseudomonas aeruginosa induces neutrophil cell death which is reversed by hypoxia. (15th November 2016) - Williams, SP; Dickinson, R; Walmsley, SR
Abstract : Introduction: Neutrophils accumulate in the lungs of patients with bronchiectasis and cystic fibrosis, and the resulting inflammation causes tissue hypoxia. Neutrophils have a unique ability to survive and function in such hypoxic environments, a response regulated by the hypoxia-inducible transcription factor (HIF)/hydroxylase oxygen sensing pathway. Pseudomonas aeruginosa is an opportunistic pathogen which colonises patients with chronic lung disease, including cystic fibrosis. It secretes the toxin pyocyanin, which induces neutrophil apoptosis in an oxygen-dependent manner, as a means of immune-evasion. P. aeruginosa has recently been shown to possess hydroxylase-homologs, suggesting that prokaryotes may also have oxygen-sensing capabilities. A prolyl-hydroxylase (PHD) - deficient strain secretes higher levels of pyocyanin compared with wild-types. We hypothesised that PHD - deficient P. aeruginosa induces a higher degree of neutrophil death compared with an otherwise genetically identical wild-type strain. Furthermore, we postulated that the killing effects of these bacteria are reversed in hypoxia. Methods: Human neutrophils were purified from healthy volunteers by discontinuous percoll gradients. PAO-1 and PHD-deficient strains were grown in lysogeny broth and equivalent growth curves confirmed. Supernatants from wild-type and PHD-deficient P. aeruginosa were harvested at two hours and then co-cultured with neutrophils in normoxia and hypoxia. Neutrophil viability and apoptosis was then assessed using AnnexinV/To-pro-3 staining on flow cytometry at three and five hours. Results: Control neutrophils in normoxia saw a decrease in viability of 6% between three and five hours. Neutrophils treated with supernatant from the PHD-deficient strain experienced a decrease in viability from 3139 (± 968) cells at three hours to 2058 (± 586) at five hours – a decline of 34% (P < 0.05). Normoxic neutrophils treated with the wild-type strain, however, saw a decrease of 21% (P < 0.05). Hypoxic conditions reversed the killing effects of wild-type P. aeruginosa: after five hours neutrophils in normoxia experienced a 21% decrease in viability, whereas the viability of hypoxic cells only decreased by 8% (P < 0.05). Discussion: These data highlight the relationship between tissue oxygen tensions and host immunity and that bacteria have evolved virulence factors with novel mechanisms of action; namely preventing neutrophil survival at sites of inflammation. Moreover, the potential oxygen-sensing capabilities of prokaryotes are intricately linked to bacterial virulence.